Love Somebody - Roasek, Rachel (New York : Farrar Straus Giroux Books for Young Readers, 2022)
Seventeen-year-old overachiever Sam attemtps to encourage a love connection between her athletic ex-boyfriend Christian and her academic rival Ros while trying not to fall for Ros herself.
Grades 10-12.
Keywords: Online identities -- Fiction; Social media -- Fiction; Bisexuality -- Fiction; Schools -- Fiction; Dating (Social customs) -- Fiction; High schools -- Fiction; Novels